2012
DOI: 10.1055/s-0032-1319911
|View full text |Cite
|
Sign up to set email alerts
|

Baseline MRI Characteristics in Asymptomatic Subjects as Predictors for Future First-Time LBP Episode

Abstract: Introduction Previously, it has been noted that there is no predictive value of MRI findings of degenerative changes of the lumbar spine in asymptomatic individuals in the development of first time episodes of low back pain (LBP). In a population-based cohort, this study addressed if radiographic findings on MRI in asymptomatic individuals are predictive in the development of first-time episodes of LBP and pain severity. Materials and Methods A prospective, radiographic and clinical study was performed in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…These results are consistent with another study that used an annular puncture model with NP removal that found a correlation between IVD degeneration and mechanical hyperalgesia, which was assayed directly on the low back . The multiple associations of pain with IVD structural and biochemical degenerative changes in this in vivo rat model have many similarities with painful IVD degeneration in humans, which supports the feasibility of using this rat model to understand the pathophysiology of discogenic pain . The lack of significant herniation or endplate damage in the observed IVD degeneration in this study is suggestive of intradiscal pro‐inflammatory cytokines as a cause for pain.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with another study that used an annular puncture model with NP removal that found a correlation between IVD degeneration and mechanical hyperalgesia, which was assayed directly on the low back . The multiple associations of pain with IVD structural and biochemical degenerative changes in this in vivo rat model have many similarities with painful IVD degeneration in humans, which supports the feasibility of using this rat model to understand the pathophysiology of discogenic pain . The lack of significant herniation or endplate damage in the observed IVD degeneration in this study is suggestive of intradiscal pro‐inflammatory cytokines as a cause for pain.…”
Section: Discussionsupporting
confidence: 90%
“…46 Samartzis et al have also noted that disk degeneration severity in asymptomatic individuals is predictive for future first-time LBP episodes. 47 These trends appear generalizable as Takatalo et al have noted for the Northern Finnish Birth Cohort that the severity of disk degeneration on MRI is associated with the severity of low back symptoms over a 3-year period in young adults. 18 What's more, a systematic review by Chou et al, addressing the association of disk degeneration on MRI and symptoms in various populations throughout the world, observed a significant association between disk degeneration and chronic LBP.…”
Section: Anatomy and Physiology Of The Intervertebral Disksupporting
confidence: 55%
“…However, more recent studies based on large populations (over 2,500 Southern Chinese subjects) have shown that disk degeneration on MRI is significantly associated with LBP history in adults, and such an association increases according to the global severity of disk degeneration (i.e., degenerative disk disease score) 46. Samartzis et al have also noted that disk degeneration severity in asymptomatic individuals is predictive for future first-time LBP episodes 47. These trends appear generalizable as Takatalo et al have noted for the Northern Finnish Birth Cohort that the severity of disk degeneration on MRI is associated with the severity of low back symptoms over a 3-year period in young adults 18.…”
Section: Anatomy and Physiology Of The Intervertebral Diskmentioning
confidence: 81%
“…In fact, both global severity [10,11] and patterning [38] of lumbar DD are associated with increased risk of LBP. For example, a large-scale 4-year prospective study among asymptomatic Southern Chinese adults by Samartzis et al [39] has reported that baseline patterns of DD may predict future development of first-time LBP episodes. This indicates that although overall DD may not be synonymous with LBP, perhaps, specific degeneration patterns and severity may foretell a pain risk profile.…”
Section: Epidemiological Studiesmentioning
confidence: 99%